2012
DOI: 10.1104/pp.112.193235
|View full text |Cite
|
Sign up to set email alerts
|

On the Discordance of Metabolomics with Proteomics and Transcriptomics: Coping with Increasing Complexity in Logic, Chemistry, and Network Interactions Scientific Correspondence

Abstract: We suspect that many biologists who have been following the development of functional 'omics and systems biology are wondering why, compared with the success in integrating information from large-scale studies of transcripts and, more recently, proteins, there is less success in integrating information about metabolism.Information about thousands of transcripts has been integrated into large databases that are used by thousands of scientists (Zimmermann et al., 2004). Rapid advances will soon allow a similar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(129 citation statements)
references
References 68 publications
(64 reference statements)
5
123
0
Order By: Relevance
“…Of the secondary metabolites that were significantly different in AM leaves as compared with control leaves, only two out of 41 were altered in a similar manner in the P i treatment (Table III). Some discordance observed between transcriptomic and metabolomic results could be explained by posttranslational modifications regulating the activity of enzymes as well as metabolite fluxes (Fernie and Stitt, 2012). A previous metabolomics study on Plantago major leaves under mycorrhization with R. irregularis (Schweiger et al, 2014a) found 40% of the AM metabolites (mostly primary metabolites) in P i -treated plants, which was explained on the basis of similar P i concentrations in leaves of the two treatments.…”
Section: Discussionmentioning
confidence: 92%
“…Of the secondary metabolites that were significantly different in AM leaves as compared with control leaves, only two out of 41 were altered in a similar manner in the P i treatment (Table III). Some discordance observed between transcriptomic and metabolomic results could be explained by posttranslational modifications regulating the activity of enzymes as well as metabolite fluxes (Fernie and Stitt, 2012). A previous metabolomics study on Plantago major leaves under mycorrhization with R. irregularis (Schweiger et al, 2014a) found 40% of the AM metabolites (mostly primary metabolites) in P i -treated plants, which was explained on the basis of similar P i concentrations in leaves of the two treatments.…”
Section: Discussionmentioning
confidence: 92%
“…By contrast, the absolute variation in metabolite abundance across the population was much greater for secondary metabolites, which showed increases of up to 95-fold and decreases down to 0 (not produced) of the level found in the recurrent parental line (while for primary metabolites the maximal increases and decreases were 17.7 and 0.18, respectively). Two factors that may explain this are (1) that secondary metabolite abundance is under considerably less intricate control, which is dominated by transcriptional regulation; and (2) the prominence of unbranched pathways in secondary metabolism provides a better concordance of transcript and metabolite levels in these pathways (Fernie and Stitt, 2012). Additionally, the secondary metabolite data displayed a different pattern of change being dominated by decreases as opposed to the tendency to increase observed in the primary metabolite data set (Schauer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our transcriptomic analysis suggests an up-regulation of the expression of genes encoding TCA cycle components. However, changes in gene expression do not always correspond to changes in protein abundance (Fernie and Stitt, 2012). This absence of correlation is especially true for mitochondrial proteins (Lee et al, 2008).…”
Section: Regulation Of Respiratory Pathwaysmentioning
confidence: 98%